ELECTRICAL TEST PADA PROSES PERBAIKAN MOTOR INDUKSI ROTOR SANGKAR 3300 V 750 KW - , NURUL ANNISA RAHMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The electric motor is an important device in industry. Therefore maintenance of electric motors on a company it is important that the production process can proceed smoothly. Damage to a electric motor is usually caused due to poor insulation on the motor windings. Damage to a electric motor can be seen visually and by measurement. Measurement was conducted on the insulation resistance, resistance test, surge comparison test and high potential test. On occasion this internship program, author do a final project in the form of case studies on electrical test on three phase induction motors with 3300 volt input voltage and output power of 750 kW at which these motors have occurred between short between the phase coil.Measurement process was conducted on the insulation resistance, resistance test, surge comparison test and high potential test. Measurement were taken before the repair and after doing a repair. So that the results of these measurements can determine whether or not a motor. In the process of this measurement using this standard of Electrical Apparatus Service Association (EASA).